Developing Support Systems for Rural Teachers’ Continuing Professional Development - Vijayan. K., (INDIAN EDUCATIONAL REVIEW, 2015)
Continuous professional development is an essential component for ensuring professionalism including teaching profession. Professional development enables teachers to continuously acquire, expand and extend their knowledge and to develop skills and abilities with the aim of improving the quality of both teaching and learning, as well as the achievements of all students. It also provides an opportunity to acquire knowledge and skills to ensure quality, to improve the relationship with colleagues, school management, parents and local communities. This helps the teachers to prepare for the acceptance of changes in the education system, successful implementation of the revised practices and active participation and initiative in carrying out these changes. Organising professional development programmes and reaching it to all teachers of the country is a biggest challenge of many of the developing and under developed nations.